Secrets of a perfect night eaudiobook - Laurens, Stephanie (Tantor Media, 2020)
Three spectacular stories all set on New Year's Eve. First, Stephanie Laurens enthralls us with a New Year's scandal, when a rake awakens in the bed of the temptress who seduced him years before. Then, Victoria Alexander enchants with her tale of a love promised, then foiled and then rekindled on another midnight. And Rachel Gibson delights with the reunion of two estranged friends and the passionate sparks that fly when the clock strikes twelve.